'Boom‐and‐busted' dynamics of phytoplankton–virus interactions explain the paradox of the plankton. Issue 3 (9th March 2022) - Flynn, Kevin J.; Mitra, Aditee; Wilson, William H.; Kimmance, Susan A.; Clark, Darren R.; Pelusi, Angela; Polimene, Luca
Summary: Rapid virus proliferation can exert a powerful control on phytoplankton host populations, playing a significant role in marine biogeochemistry and ecology. We explore how marine lytic viruses impact phytoplankton succession, affecting host and nonhost populations. Using an in silico food web we conducted simulation experiments under a range of different abiotic and biotic conditions, exploring virus–host–grazer interactions and manipulating competition, allometry, motility and cyst cycles. Virus‐host and predator–prey interactions, and interactions with competitors, generate bloom dynamics with a pronounced 'boom‐and‐busted' dynamic (BBeD) which leads to the suppression of otherwise potentially successful phytoplankton species. The BBeD is less pronounced at low nutrient loading through distancing of phytoplankton hosts, while high sediment loading and high nonhost biomass decrease the abundance of viruses through adsorption. Larger hosts are inherently more distanced, but motility increases virus attack, while cyst cycles promote spatial and temporal distancing. Virus control of phytoplankton bloom development appears more important than virus‐induced termination of those blooms. This affects plankton succession – not only the growth of species infected by the virus, but also those that compete for the same resources and are collectively subjected to common grazer control. The role of viruses in structuring plankton communities via BBeDs can thus provide an explanation for the paradox of the plankton.